A Comparative Study to Evaluate The Results of Skin Pigmentation Resulting From Thigh Friction (Meta-Analysis) - Mohammed, Dr. Rusul Sahib Hussien (Central Asian Journal of Medical and Natural Science, 2025)
Frictional melanosis of the inner thighs is an under-recognized pigmentary disorder predominantly affecting females, characterized by hyperpigmentation resulting from repeated mechanical friction ,Despite its frequent clinical occurrence, it remains poorly documented in the literature, with unclear pathogenesis and limited consensus on management where this study aims to comparatively evaluate the clinical features, severity, and contributing factors of skin pigmentation caused by thigh friction, integrating clinical, anthropometric, and histopathological data to better understand its ethology and implications as well as our study Methods refer to meta-analysis for patients presenting with frictional melanosis of the inner thighs where Clinical examination, were performed, Body mass index (BMI) was recorded to assess the relationship between obesity and pigmentation severity threfore Data on friction exposure and associated skin conditions were collected through structured interviews, where in our study The table provides the comparative results reported in the studies, including pigmentation effects and practical implications across these studies. It summarizes the findings and further translates these findings into clinical or preventative recommendations focusing on the relationship between friction, obesity, and the degree of pigmentation so we concloude Frictional melanosis of the inner thighs is a distinct clinical entity strongly associated with mechanical friction and obesity in addition to Early recognition and preventive strategies focusing on weight management and friction reduction are essential and Further research is warranted to establish standardized diagnostic criteria and effective treatment modalities.